Building the future: Toward a sustainable material transition in architecture and construction - Cordula Kropp; Simon Aicher (TATuP – Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis)
In the introduction, we discuss the need for a material transition in architecture and construction and the challenges it poses. Drawing on innovation research, the multi-level perspective (MLP), and thousands of years of building history, we identify the potential for change, the obstacles that need to be overcome, and the importance of standards, in particular of established industry standards. The introduction also includes a brief description of each article.